Investigation of the effects of Bipolar Radiofrequency Energy on the Structural Morphology of Dental Plaque - Amaechi, Bennett T.; Mohseni, Sahar; Dillow, Andrew M.; Abdul Azees, Parveez Ahamed; Movaghari Pour, Fatemeh; Kataoka, Yuko; Restrepo, Maria Camila (European Journal of Dentistry, 2023)
Objectives To investigate the effects of radiofrequency (RF) energy, applied through a power toothbrush, on the structural morphology of dental plaque and its bacteria components. Previous studies showed that a toothbrush powered by RF (ToothWave) effectively reduces extrinsic tooth stains, plaque, and calculus. However, the mechanism by which it reduces dental plaque deposits is not fully established.Materials and Methods Multispecies plaques at sampling time points of 24, 48, and 72 hours were treated with the application of RF using ToothWave with the toothbrush bristles 1 mm above the plaque surface. Groups that underwent the same protocol but without RF treatment served as paired controls. Confocal laser scanning microscope (CLSM) was used to determine cell viability at each time point. Plaque morphology and bacteria ultrastructure were viewed using scanning electron microscope (SEM) and transmission electron microscope (TEM), respectively.Statistical Analysis Data were analyzed statistically using analysis of variance (ANOVA) and Bonferroni post-tests.Results At each time, RF treatment significantly (p < 0.05) reduced the viable cells in plaque and caused a substantial disruption of plaque morphology, while the untreated plaque had intact morphology. Cells in treated plaques showed disrupted cell walls, cytoplasmic material, huge vacuoles, and heterogeneity in electron density, while these organelles remained intact in untreated plaques.Conclusion The application of RF via a power toothbrush can disrupt plaque morphology and kill bacteria. These effects were enhanced by the combined application of RF and toothpaste.
Keywords: dental plaque; power toothbrush; radiofrequency; toothbrushing; ToothWave; bacterial viability